Community Journey of Change Through Relational Determinants of Health - Cardinal, Shelley; Pepler, Debra (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2021)
This article describes a model that maps Indigenous communities’ journeys from the cycle of violence arising from colonization to the circle of wellness through relational determinants of health. This model emerged from learning with Indigenous communities participating in research on violence prevention programming with the Canadian Red Cross. Indigenous communities have shown us that they are returning to a place of thriving by restoring relationality with land, culture, ceremony, and language. Therefore, the relational determinants of health comprise the foundational relationships that contribute to wellness. The Community Journey of Change model represents actions that communities can undertake in moving to wellness. The model has implications for policies, programs, and services for Indigenous communities as they begin to restore health and wellness.